Yogyakarta Urban Middle-Class Sufism: Economic, Political and Cultural Networks - Yusdani Yusdani; Hujair AH Sanaky; Edi Safitri; Imam Machali; Muhammad Iqbal Juliansyahzen (Ulumuna, 2019)
The phenomenon of strengthening religious activity in the urban middle-class society in Yogyakarta Special Region in the last decade has been remarkable. The shift from the traditional Sufism to the model of piety associated with this middle-class Sufism further reinforce the middle class's religiosity. This study focused on the problem of the middle-class Muslim community when involving in Sufi practices. Through an in-depth interview with Sufi members and observation on their Sufi practice, this study shows that the urban middle-class Sufism pattern in Yogyakarta places emphasis on aesthetic-symbolic values. On the one hand, the tendency of religious patterns of Muslim communities is a form of negotiation between the values of spirituality in Islam and the forms and practices of global culture. On the other hand, the Sufi practice constitutes negotiation of the models of piety with economic-business motives. This Sufism is not institutionalized in conventional Sufism, commonly known as sufi order (tarekat) such as qadariyya, naqshabandiyya, and shattariyya, among the most popular Sufi order. Middle-class Sufism frames their distinctiveness in the form of economic, political, and cultural networks.